Scientific Opinion on the safety of refined Buglossoides oil as a novel food ingredient. (25th February 2015) - ,; ,
Abstract: Following a request from the European Commission, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver a scientific opinion on refined Buglossoides oil as a novel food ingredient (NFI) in the context of Regulation (EC) No 258/97. The NFI is produced from the seeds of Buglossoides arvensis (L.) I. M. Johnst, using processes conventionally used for edible oil production. The main fatty acids (FAs) contained in the NFI are alpha‐linolenic acid (ALA), stearidonic acid (SDA) and linoleic acid, with smaller amounts of oleic acid, gamma‐linolenic acid (GLA) and saturated FAs. With the exceptions of SDA and GLA, these FAs are widely present in common foods. The NFI is intended to be used in a range of foods and food supplements to provide approximately 200 mg of SDA per day. Upon digestion, FAs are used primarily as an energy source. ALA and SDA can be elongated and desaturated to produce eicosapentaenoic acid. In human studies using various sources of SDA, no increase or small increases in SDA were observed in blood cell membranes or in total plasma. The proposed specifications for pyrrolizidine alkaloids and erucic acid, which are undesirable substances, do not give rise to concern in view of the proposed conditions of use. The available information does not give concerns as regards other undesirable substances in the NFI. Available animal studies provide only limited information on the safety of the NFI. Human studies that investigated different plant oils or fatty acid ethyl esters as sources of SDA, GLA and ALA found no adverse effects with up to 4 200 mg SDA/day for 12 weeks, up to 1 700 mg GLA/day for 28 days and 9 100 mg ALA/day for four weeks. The Panel concludes that the NFI is safe for the proposed uses and use levels.